PENJADWALAN TRUK SAMPAH KOTA PONTIANAK DENGAN MODEL ROLL ON ROLL OFF VEHICLE ROUTING PROBLEM - -, SURLI - (Jurnal TIN Universitas Tanjungpura, 2017)
Increased consumption and need for goods that generate waste has an impact on environmental hygiene Pontianak city. Production of waste generated by the resident according to the Office of Sanitation and Park of Pontianak City in 2015 reached 1339.98 tons per day over 64 locations with a fleet of only 35 units available. This makes the process of transporting waste needs to be done effective and efisienct. The aims of this study are to analyze the exizting condition of the transport arm roll garbage truk in Pontianak City and use the model of Roll on Roll off Vehicle Routing Problem to generate better waste transportation schedule in Pontianak city.The steps in solving scheduling problem of Pontianak City garbage trucks using the model of Roll On Roll Off Vehicle Routing Problem are by mapping the locations of waste in Pontianak city, calculating the distance using the road map, describing the problem of scheduling garbage trucks, determining the types of trip used for Pontianak city garbage truck and calculating the service time of each garbage truck.Based on the research on Pontianak city garbage truck scheduling with model of Roll On Roll Off Vehicle Routing Problem, the following conclusions can be drawn: Amr roll truck fleet consisting of 22 units of vhicle, there are 8 vehicles that exceed the time limit of service, so do balancing the workload between vehicles has been conducted. This proves that amr roll waste transportation trucks in Pontianak are not optimal. The Model of Roll On Roll Off Vehicle Routing Problem has not been able to obtain the optimal schedule for a solution model using the heuristic method. However, the proposed heuristic method has been able to offer a solutions for better waste transpotation fares in the sense that it reduced the schedule of vehicles that exceed the time limit. The waste transportation services schedule originally had 8 vehicles that exceed the time limit of 80.1398 service hours to 4 vehicles that exceed the time limit of 39.0832 hour service so that there is a difference of total service time of 41.0566 hours. This proves that the scheduling for garbage transportation is better.Keywords: Scheduling, Roll On Roll Off Vehicle Routing Problem, Garbage Trucks